African Smallholders: Food Crops, Markets and Policy - Djurfeldt, Göran (CABI, 2014)
The Afrint team and the editors want to acknowledge the support of the Swedish Research Council and Swedish International Development Cooperation Agency (Sida), which, together with Lund University, ﬁ nanced the research. The work builds upon cooperation between researchers at Lund and Linköping Universities and the Ethiopian Economic Association; Addis Ababa University; African Economic Research Consortium (AERC); Department of Geography, Kenyatta University; Department of Agricultural Economics and Agribusiness, Makerere University, Kampala; Institute of Continuing Education, Sokoine University of Agriculture; Centre for Social Research and Faculty of Social Science, University of Malawi; Institute of Economic and Social Research (INESOR) and Development Studies Department, University of Zambia; EconPolicy Research Group Ltd, Maputo; Nigerian Institute for Social and Economic Research (NISER), Ibadan; Institute of Statistical, Social and Economic Research (ISSER) and Department of Agricultural Economics and Agribusiness, University of Ghana, Legon–Accra. Finally, we thank our advisors: Göran Hydén, Oliver Saasa and Richard Mkandawire.